2008
DOI: 10.1007/s10562-008-9696-x
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Activity of Catalysts on the Base of H3PW12O40 in Partial Oxidative Conversion of C3–C4 alkanes

Abstract: Catalysts from heteropoly acid H 3 PW 12 O 40 and its Cs, Na, Ba, Pb, Ca, Cd, Cr, Mn, V, La salts supported on clinoptilolite, alumosilicate are highly active in oxidative conversion of propane-butane (OCPB) mixture and formation of C 2 -C 4 olefins, oxygen-containing compounds at temperatures T = 100-800°C. Optimum yields of ethylene and propylene are achieved on heteropoly acid its Cs and Cr salts. The processes of oxidative dehydrogenation (ODPB) and cracking are concurrent in formation of olefins. High act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…23 1 H NMR (400 MHz, CDCl 3 ): d = 8.75 (s, 2H, H 3′,5′ ), 8. 2H,H 6,6″ ),2H,H 3,3″ ),2H,H Ph ),2H,H 4,4″ ),2H,H Ph2,6 ),1H,H Ph3,5 ),2H,H 5,5″ ).…”
Section: Materials and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 1 H NMR (400 MHz, CDCl 3 ): d = 8.75 (s, 2H, H 3′,5′ ), 8. 2H,H 6,6″ ),2H,H 3,3″ ),2H,H Ph ),2H,H 4,4″ ),2H,H Ph2,6 ),1H,H Ph3,5 ),2H,H 5,5″ ).…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…As solid catalysts, pure bulk POMs present relatively small surface areas (<10 m 2 g −1 ) that hinder the accessibility of substrate molecules to the active sites. Thus, various supports with high surface areas such as silica, 3 activated carbon, 4 zeolites, 5 and mesoporous molecular sieves 6 have been investigated for the dispersion and heterogeneity of POMs. However, traditional methods of immobilization often lead to many limitations, including low loading efficiency, POM leaching, inactivation of active sites and ill-defined structures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nevertheless, the application of pure POMs is limited by low surface areas as solid catalysts 3 and poor reusability as homogeneous catalysts. To overcome these drawbacks, POMs have been dispersed and immobilized to various supports with high surface areas such as zeolites, 4 silica, 5 activated carbon, 6 mesoporous molecular sieves, 7 and even metal−organic macrocycles. 8 Recently, one of the most attractive strategies for heterogenizing POMs is using metal−organic frameworks (MOFs) as host matrice.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) that possess unique metal–oxygen framework and excellent acid/oxidation catalytic properties have great application prospects in industry. , Nevertheless, the application of pure POMs is limited by low surface areas as solid catalysts and poor reusability as homogeneous catalysts. To overcome these drawbacks, POMs have been dispersed and immobilized to various supports with high surface areas such as zeolites, silica, activated carbon, mesoporous molecular sieves, and even metal–organic macrocycles . Recently, one of the most attractive strategies for heterogenizing POMs is using metal–organic frameworks (MOFs) as host matrice. , For instance, Liu and Hill et al have reported a series of highly crystalline Cu-BTC MOFs (BTC = 1,3,5-benzenetricarboxylic acid) incorporating the protonated POMs in hydrothermal synthesis and used them as effective solid catalysts for the hydrolysis and oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%